Legitimasi dan Kritik terhadap Konsep Wali Majdzub dalam Islam: Analisis Tafsir dan Diskursus Tasawuf - Tiaramillah Ryn Maulida; Mursalim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The concept of wali majdzub constitutes one of the most controversial themes in the Islamic mystical tradition due to its association with spiritual experiences considered to transcend rational consciousness and, at times, appear inconsistent with the outward norms of Islamic law (shari‘a). Some Sufi scholars regard the wali majdzub as a chosen servant of God who receives direct spiritual attraction (jadhb) from Allah SWT., while other Muslim scholars argue that the concept may lead to theological deviation and the legitimization of practices that contradict Islamic teachings. This study aims to analyze the concept of wali majdzub from the Qur’anic perspective and examine the pro and contra arguments among Muslim scholars regarding its existence. The research employs a qualitative library research method using a thematic Qur’anic interpretation (tafsir maudhu‘i) approach and a Sufi-theological discourse analysis. Primary data are derived from Qur’anic verses related to sainthood, particularly QS. Yunus [10]: 62–63 and QS. al-Kahf [18]: 60–82, as well as classical Sufi works by al-Qushayri, al-Tirmidhi, and Ibn Taymiyyah. The findings reveal that the Qur’an does not explicitly mention the term wali majdzub; however, the concept of sainthood is closely associated with faith and piety. Within the Sufi tradition, the wali majdzub is understood as a figure experiencing jadhb, namely a divine spiritual attraction affecting one’s outward consciousness. Proponents consider this condition a legitimate form of mystical experience within Islamic spirituality, whereas opponents emphasize that sainthood must remain subject to the framework of shari‘a and cannot justify deviant behavior. This study concludes that the debate surrounding wali majdzub reflects an ongoing dialectic between spiritual authority and the normative framework of Islamic law in the Islamic tradition. The research contributes to the development of Qur’anic and Sufi studies through a critical examination of the relationship between mystical experience, the legitimacy of sainthood, and theological boundaries in Islam.